The Challenge is “Now” and “In the Future” for Bioenergetic Analysis - Moselli, Patrizia (Bioenergetic Analysis, 2020)
Alexander Lowen developed his theory by observing what happened in the evolution of the child and in the construction of his/her defenses. Character defenses block vitality and therefore we could define «vitality” as the procedural memory of our «natural child” who, in the course of their development, has created so many characterological adaptations. Vitality is blocked because it is disorganized by developmental traumas that prevent the natural process of adaptation generated by a loss of love and by attachment disorders. So, working with the life force becomes the center of the therapeutic process, since our vitality is blocked by disorganized defenses that we could consider to be real post-traumatic stress syndromes. Rebuilding «safe relationships” becomes fundamental to create that energy field in which the individual can experience his/her «asleep” vitality. The therapist must be able to convey bonds of attachment that can connect the patient to both humanity and to nature. The therapeutic relationship explores the nature of these bonds, which is fundamentally sensory and emotional, intrinsically «intelligent”, as guided by profound regulatory processes.